Association between tobacco usage and dental caries among 35-44-year-old fishermen of North Coastal Region of South Indian State, Andhra Pradesh - Asha Lodagala; Srinivas Pachava; Devaki Talluri; Viswa Chaitanya Chandu (Wolters Kluwer Medknow Publications, 2018)
Introduction: Tobacco usage is popular among rural and urban communities of India. Sporadic studies that were conducted to know the caries experience among tobacco users yielded conflicting conclusions. Fisherfolk communities form a special population in light of the variations in their dietary habits compared to general population. Aim: The aim of this study was to explore the dental caries (DC) experience among tobacco users and nonusers in fisherman communities residing in the north coastal region of a south Indian state. Materials and Methods: A comparative cross-sectional survey was done in fisherman community belonging to a north coastal region of a South Indian state. Stratified randomized sampling technique was employed to recruit 374 adult participants aged 35-44 years. The survey included interviewer-administered questionnaire and clinical examination for measuring DC experience. The questionnaire consisted of demographic data, brushing aids, 2 days sweet score, and a detailed record on tobacco use of subjects. Decayed missed and filled index (DMFT) and Simplified Oral Hygiene Index (OHI-S) were recorded. The study participants were dichotomized based on tobacco usage. The tests used were independent samples t-test, analysis of variance, and Chi-square test. Results: DC was present among 46.5% of tobacco users and 65.8% of nonusers. The mean DFT score for tobacco users (0.62 ± 0.23) was less when compared to that of nonusers (1.40 ± 0.52) after excluding missing component, which is statistically significant (P < 0.001). The mean OHI-S was higher among tobacco users than nonusers. There was no statistically significant difference in the mean sweet scores between these two groups (P = 0.172). Conclusion: Despite higher mean OHI-S scores among tobacco users and similar sweet scores among both the groups, DC experience among tobacco users was less when compared to nonusers. Longitudinal studies are recommended for further confirmative evidence.